GESTÃO ESTRATÉGICA DE MEIO AMBIENTE E SEGURANÇA: REFLEXÃO INCLUINDO GESTÃO DE PERDAS - Netto, Washington Blanco Lima (2005)
The environment and the prevention of accidents of the work and occupational diseases have become at the beginning of this century, one of the most urgent subjects to establish a high level of competitiveness between the companies. Rarely, or never, an administrative problem is only product of a cause, including those related with the safety, production or quality. The practice has been taking us to accept the following conclusions: the incidents that deteriorate our business are caused, they don t happen without a plausible cause and the causes of the losses can be determined and controlled. The objective of the work is to discuss a basic structure of a model to be applied to the Environment and Occupational Health and Safety of the Work, that it can t be isolated of the other activities of the Organization, and not only worked straight on the human mistake. We should look for a hybrid model, involving the responsibility of the administration in the greater objective of reaching the goals of reduction of accidents and improvement of the work conditions.